2016
DOI: 10.1177/1934578x1601101223
|View full text |Cite
|
Sign up to set email alerts
|

A New Lactone from Chaetomium globosum Strain M65 that Inhibits the Motility of Zoospores

Abstract: In a search for endophytes from medicinal plants of Bangladesh, we isolated the M65 fungal strain from the fruit of Azadirachta indica. Following chemical screening, chromatographic purification of the culture extract of strain M65 led to the isolation of the previously reported lasiodiplodin (2), the known derivative 1, and the new derivative 3a, along with two further known compounds (4 and 5). The new (3R,5R)-5-hydroxylasiodiplodin (3a), the enantiomer of the known (3S,5S)-5-hydroxylasiodiplodin (3b), inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…2) that revealed key NOE correlations between H-2 and H-5 indicating that they are facing the same plane of the structure while another key NOE correlation was noticed between a doublet methyl at C-2 and the methylene group H 2 -7. By comparing the obtained 1D/2D NMR data and optical rotation of 2 to all possible stereoisomers of cyclo-(Ala-Trp) that have been previously described, 15,16 compound 2 was unambiguously conrmed to feature (2R,2R) conguration and hence was trivially named as cyclo-(D-N-OH-Ala-D-Trp). To the best of our knowledge and by searching the reported literature, this is the rst report of 2 as a natural product while it was formerly patented among other synthetic derivatives for the prevention and treatment of nephritis.…”
Section: Structure Elucidation Of Compoundsmentioning
confidence: 78%
See 2 more Smart Citations
“…2) that revealed key NOE correlations between H-2 and H-5 indicating that they are facing the same plane of the structure while another key NOE correlation was noticed between a doublet methyl at C-2 and the methylene group H 2 -7. By comparing the obtained 1D/2D NMR data and optical rotation of 2 to all possible stereoisomers of cyclo-(Ala-Trp) that have been previously described, 15,16 compound 2 was unambiguously conrmed to feature (2R,2R) conguration and hence was trivially named as cyclo-(D-N-OH-Ala-D-Trp). To the best of our knowledge and by searching the reported literature, this is the rst report of 2 as a natural product while it was formerly patented among other synthetic derivatives for the prevention and treatment of nephritis.…”
Section: Structure Elucidation Of Compoundsmentioning
confidence: 78%
“…By comparing the obtained NMR data of 2 with the reported literature, it was found to be very similar to cyclo(D-Ala-D-Trp) ( 3 ) that was previously reported as a fungal metabolite produced by an endophytic fungus Chaetomium globosum from the fruits of Azadirachta indica . 15 By comparing NMR data and molecular formulas of 2 and cyclo(D-Ala-D-Trp) ( 3 ), it was found that the former has an additional oxygen atom interpreting the difference of 16 atomic units in their molecular weights while their NMR data were closely similar except in the appearance of a deshielded exchangeable proton at δ H 9.83 in 2 replacing one exchangeable amide NH proton in the diketopiperazine moiety indicating that one amide NH is converted to N–OH functionality. To unambiguously define the position of N–OH group in 2 , 1 H– 1 H COSY spectrum was measured in DMSO- d 6 that revealed an obvious spin system from an exchangeable NH proton at δ H 8.28 (br d, J = 2.5 Hz, 6-NH) to an aliphatic methine at δ H 4.21 (q, J = 3.7 Hz, H-5) and extending to the methylene group at δ H 3.03/ δ H 3.24 (H 2 -7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation